TRANSFORMASI DIGITAL UMKM FLORIST : IMPLEMENTASI SISTEM PEMESANAN DAN TRANSAKSI BERBASIS APLIKASI UNTUK MENDUKUNG WIRAUSAHA BERBASIS TEKNOLOGI - Agustian Syahputra; Muhammad Thaherudin; Siti Nurul Khotimah; Muhamad Bintang Saputra; Kurnia Rachmadani, (PEMTEKDIKMAS (PENGABDIAN EKONOMI MULTIDISIPLIN TEKNOLOGI PENDIDIKAN UNTUK MASYARAKAT), 2024)
Digital transformation represents a critical imperative for micro-enterprises seeking competitive advantage and sustainable growth in increasingly digital markets. This Community Service Program (PKM) advanced previous capacity-building efforts at Toko Bunga Fajar Florist through implementation of an integrated digital ecosystem encompassing online ordering, secure payment processing, and real-time transaction management. The program focused on: (1) comprehensive digital transformation strategy development; (2) integrated application development with payment gateway integration; (3) advanced training on fintech-enabled business operations; and (4) sustained mentoring for technology-based entrepreneurship development. The integrated system, "FloraHub Pro," incorporates: multi-channel ordering (web, mobile, social media), integrated payment systems (e-wallet, bank transfer, card payments), inventory management synchronized with sales, customer analytics with predictive insights, and automated financial reporting. Implementation involved 5 participants (1 owner, 2 creative staff, 2 administrative staff). Results after 8 weeks demonstrated: transaction volume increased 52%, average transaction value increased 45%, payment success rate reached 99.2%, customer lifetime value increased 340%, operational costs reduced 18%, and business confidence in technology increased significantly (score 8.9/10). Training participant satisfaction reached 92% with 95% competency achievement. This program validates that technology-enabled entrepreneurship through integrated digital systems enables micro-enterprises to achieve scalable, sustainable business models.